Senior and youth national team competitive experience: influence on player and team performance in European basketball championships - Kalén, A.; Pérez-Ferreirós, A.; Rey, E.; Padrón-Cabo, A. (International Journal of Performance Analysis in Sport, 2017)
This study aimed to discover if the number of previous senior and youth national team championships played relates to the team and player performance at the European basketball championships. The sample consisted of all national teams and their players participating in the 2011, 2013 and 2015 European Championships for men (teams n = 72; players n = 697) and women (teams n = 52, players = 520). The teams were classified into four groups based on their highest stage reached in the tournament. A k-means cluster was used to group the players as high, medium or low performers according to their efficiency rating. The number of previous senior and youth championships was compared between groups. Better performing teams and players had a higher number of previous senior championships. The competitive experience differentiates low performing players for both genders, but only distinguishes high from medium performing players for women. No differences in the number of youth championships were found. It appears to be critical to have a sufficient amount of accumulated senior competitive experience within the team to reach the semi-final phase both for men`s and women`s national teams.